Peningkatan Hasil Belajar Pembagian Pecahan Biasa dengan Pendekatan Konstruktivisme di Kelas V SD Negeri 03 Silaut Kabupaten Pesisir Selatan - Sulistya Sulistya (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
The research is based on the low learning result of  Fractional Sharing Division, because in learning the students do not have the opportunity to communicate their initial knowledge and build their own understanding. To overcome this, researchers through this research apply the approach of Constructivism to improve learning outcomes. The purpose of the study describes the planning, implementation, and improvement of learning outcomes of regular fractional divisions in class V with a constructivism approach. The research type is Classroom Action Research using the qualitative and quantitative approach. Subjects of teachers and 21 students of class V. Techniques of data collection using observation, tests, documentation. Data analysis using qualitative data analysis is data reduction, data presentation, a conclusion. Quantitative data analysis is a descriptive analysis. Research carried out II cycle. Each cycle consists of planning, execution, observation, reflection. The results showed that from cycle, I to cycle II, it can be concluded that constructivism approach can improve learning result of fractional division in class V SDN 03 Kecamatan Silaut.